STRATEGI PEMBERDAYAAN EKONOMI RAKYAT DALAM PENANGGULANGAN KEMISKINAN DI INDONESIA - Ni Ketut Rendi Astuti; Ni Made Gunastri (Forum Manajemen, 2014)
Pervasive poverty remains a major challenge to the efforts of developmentin Indonesia. An economic empowerment for the people is something that must bedone, in order to obtain a national economic recovery. The growth of Indonesianeconomy that had been rapid before the financial crisis led to a state of oblivion madeby those economic agents and institutions functioned as the policy holders. While,on the other hand, negligence occurred as they had been shown in the economicactivities from the agents, which were unsupervised and out of control. Exchange rate crisis had turned into the most complex economic crisis ever experienced by Indonesia, at least since the New Order era empowered. This economic crisisultimately created a great economic recession by itself and increased the level ofpoverty and gap in the income distribution in the country. Fourteen years passedthe Reformation Era, but these had not still been able to touch all of the aspects ofnational life. Only the formal legal issues reformed neatly. However, the main issues,such as corruption, poverty, unemployment and injustice could not still done untilthe Indonesian nation has completely reformed in total. Traditional sector, whichwas firstly considered unimportant as a barrier to the economic growth, later itplayed an important role in tackling with the poverty. Based on a study conductedby a number of economists, strategies within the citizen economic empowermentto cope with poverty in Indonesia are formulated through one policy package thathas a characteristic of complimentary and they support each other, so that, they arecapable to deal with the level of poverty in Indonesia.